2022
DOI: 10.1039/d1py01659h
|View full text |Cite
|
Sign up to set email alerts
|

New mechanism for autoxidation of polyolefins: kinetic Monte Carlo modelling of the role of short-chain branches, molecular oxygen and unsaturated moieties

Abstract: In this work, a bivariate kinetic Monte Carlo (kMC) model is constructed to study autoxidation, which is the degradation of polymers in the presence of oxygen. The use of computational...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…A recent work featuring a kinetic model based on ab initio results for molecules stresses the importance of this pathway, and also previous studies have shown that taking into account reaction 1b is important for reproducing experimentally some observed autoacceleration effects in the oxidation process. In particular, this reaction was introduced in kinetic models of radio-oxidation in order to correctly predict the radio-chemical yields of oxidation products and chain scission and to account for the non-Arrhenius behavior of the oxidation induction time and of the oxidation rate …”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…A recent work featuring a kinetic model based on ab initio results for molecules stresses the importance of this pathway, and also previous studies have shown that taking into account reaction 1b is important for reproducing experimentally some observed autoacceleration effects in the oxidation process. In particular, this reaction was introduced in kinetic models of radio-oxidation in order to correctly predict the radio-chemical yields of oxidation products and chain scission and to account for the non-Arrhenius behavior of the oxidation induction time and of the oxidation rate …”
Section: Resultsmentioning
confidence: 89%
“…Some of these mechanisms were investigated in a recent paper 19 of which we became aware during the review process. The outcome, for PE, relying on a careful kinetic model based on reaction rates from the literature and from ab initio calculations globally support our conclusions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of groups working to address O 2 effects in reaction kinetics is focused on photopolymerization. There are reports of very small amounts of O 2 affecting solution RAFT polymerization by permeation through a continuous flow microreactor wall and of modeling of particle size distribution during emulsion vinyl chloride polymerization, and kinetic Monte Carlo was used to study autoxidation of polyolefins . Nonetheless, there are few studies quantitatively investigating how O 2 affects reaction kinetics, through continuous reaction monitoring, as done in this work.…”
Section: Introductionmentioning
confidence: 99%
“…As this was much lower than what was observed during our reactivity study, O 2 seemed to be the more likely origin of the enhanced degradation. Pyrillium catalysts are known to sensitize 1 O 2 , which can form reactive peroxide species that promote polymer cracking. , To investigate the possibility of analogous reactivity under our conditions, samples of 1 (25.1 mg; 0.27 mmol), 2 (5.5 mg; 0.014 mmol), and (PhS) 2 (15.2 mg; 0.07 mmol) were dried over P 2 O 5 for 16 h. The dried reagents were dissolved in anhydrous DCM (0.075 M) in a glovebox and irradiated with blue light under a balloon of anhydrous O 2 . After irradiation for 1 h, SEC analysis revealed a 96% reduction in M n relative to 1 (Δ M n = −113 kDa; Figure S10), which mirrored the enhanced activity we originally observed under ambient conditions (Table ).…”
mentioning
confidence: 99%